A Remark on a Functional Equation Related to Digital Filtering - Naenudorn, Khanithar; Hengkrawit, Charinthip (Thai Journal of Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH <![endif]--> Abstract In this paper, by using the technique of Haruki and Nakagiri in 2007, we show that the functional equation related to digital filtering … is equivalent to the following equations: … and … Keywords: functional equation; translation (shift) operators; functional equation related to digital filtering; wave equation <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->